2016
DOI: 10.1016/j.ijso.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of orthopaedic elective and trauma operative notes: A completed audit loop study

Abstract: Introduction: Good medical practice dictates that comprehensive documentation of all surgical procedures is paramount in maintaining a high standard of patient care. This study audited the quality of operative note keeping for elective and trauma procedures against the standards set by the British Orthopaedic Association (BOA) and The Royal College of Surgeons of England (RCSE) guidelines. Patients and methods: A retrospective assessment of the operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…A heading or specific textbox for the serial numbers may present a solution to this and one that would be easy to implement. Shah, et al also reported low documentation numbers for serial numbers of prostheses used in orthopaedic surgeries [6]. Their numbers were lower initially but did improve on re-audit whereas our numbers remained low.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…A heading or specific textbox for the serial numbers may present a solution to this and one that would be easy to implement. Shah, et al also reported low documentation numbers for serial numbers of prostheses used in orthopaedic surgeries [6]. Their numbers were lower initially but did improve on re-audit whereas our numbers remained low.…”
Section: Discussionmentioning
confidence: 60%
“…Proforma benefits pertaining to operative documentation have been highlighted in other surgical specialties previously [11-12]. Shah, et al have shown statistically significant improvement in orthopaedic operation note documentation when using the British Orthopaedic Association guidelines and the RCS guidelines as a template for their total knee replacement (TKR) and total hip replacement (THR) operation notes [6]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many electronic health systems enforce compliance by using drop down selections with failure to close pop out windows if incompletely filled14. Introduction of an electronic based template improves the standards of documentation and education of surgeons18,19. The major limitation of this study is that, although the operative notes written by the authors were excluded to counteract and eliminate bias, the unavailability of a second independent assessor for collateral and simultaneous assessment of the operative notes opens to analytical biasness.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been studies looking into documentation in orthopaedics against BOA guidelines [ [6] , [7] , [8] ], 2008 RCS Good Surgical practice guidelines [ 9 , 10 ] and 2014 RCS Good Surgical Practice guidelines [ 8 , 11 ]. However, to our knowledge we are the first orthopaedic unit to study documentation of hip arthroplasty against July 2019 GIRFT, BHS and BOA guidance.…”
Section: Introductionmentioning
confidence: 99%